Effect of Different Cooling Rates Condition on Thermal Profile and Microstructure of Aluminium 6061 - Benjunior, B.; A. H., Ahmad; Mohd Rashidi, Maarof; Mohamed Reza Zalani, Mohamed Suffian (Elsevier Ltd, 2017)
Thermal analysis and microstructure characterization provide information regarding material thermal profiles and microstructure formation. Wrought aluminium alloys offer significant advantages in terms of higher ultimate tensile strength (UTS) and yield strength but relatively poor fluidity properties. The objective of this experiment presented in this paper was to understand the relationship between solidification rate, metallurgical behaviour, and fraction phase growth of wrought aluminium 6061. This information was crucial and important to the foundry industry to understand the material behaviour that will help to cast wrought aluminium 6061. Thermal analysis and microstructure of wrought aluminium 6061 on different cooling conditions are present in this paper. In this work, Aluminium 6061 heated and melted in a graphite crucible at a temperature of 800 °C. Two thermocouples located at the centre and 20 mm from the graphite crucible wall. Slow cooling rate condition experiment rig was developed by placing graphite crucible into a chamber with kaowool insulation. Normal cooling rate condition was developed by allowing the molten solidify at room temperature. Fast cooling rate condition was prepared by applying a forced airflow over the graphite crucible. The slow, normal, and high cooling rates were calculated at 0.03 °C/s, 0.2 °C/s and 0.3 °C/s respectively. Cooling curve analysis was performed to predict various areas of solidification phase and fraction solid. In Addition, the microstructure formation was observed, recorded, and compared between different cooling conditions. The results show slow cooling rate condition formation of eutectic and solidus temperatures occurred far from liquidus temperature. The eutectic and solidus temperature was increased with the increment of the cooling rate. Furthermore, the DCP temperature of slow cooling rate condition at 638.3 °C was the lowest while gives wider temperature range corresponding to the fraction solid percentage increment. Meanwhile, an increase in cooling rate refined the microstructure, improved the grain circularity and at the same time reduced the aspect ratio.